A critical analysis of the obligation and liability of the carrier under the Rotterdam Rules - Ahmad, Muhamad Hassan; Masum, Ahmad; Mohamed Nafees, Seeni Mohamed; Ali Mohamed, Ashgar Ali (Lexis Nexis Malaysian Sdn Bhd, 2019)
The United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea 2008 (‘the Rotterdam Rules’) facilitates modern alternatives and provides substantial changes to the Hague Rules, the Hague-Visby Rules and the Hamburg Rules from various perspectives. Nonetheless, it is not yet in force to this day as major maritime countries are generally not in favour of the rules as it increases the obligation and liability of carriers. Accordingly, this paper evaluates to what extent the carrier’s obligation and liability is extended under the Rotterdam Rules. In fact, the obligation and liability of the carrier envisaged under these rules provide the balance of interest between shipping companies and shippers. Therefore, authors propose that it is beneficial for States which have little or no maritime transportation industry to go for ratification, acceptance, approval or accession of the Rotterdam Rules.